Monthly Extended-Release Risperidone (RBP-7000) in the Treatment of Schizophrenia: Results From the Phase 3 Program. Issue 5 (September 2019) - Andorn, Anne; Graham, Jay; Csernansky, John; Newcomer, John W.; Shinde, Sunita; Muma, Gilbert; Heidbreder, Christian; Fava, Maurizio
Abstract: Purpose/Background: The Phase 3 program for RBP-7000, a once-monthly subcutaneous (SC) extended-release risperidone formulation approved for treatment of schizophrenia, consisted of a double-blind placebo-controlled trial (previously reported) and a 52-week open-label study of monthly RBP-7000 120 mg. The primary objective of the open-label study was to evaluate the long-term safety and tolerability of RBP-7000 in adults with schizophrenia. A secondary objective was to assess long-term maintenance of effectiveness. Methods/Procedures: The 52-week Phase 3 open-label study (NCT02203838) enrolled 92 rollover participants from the double-blind trial (NCT02109562) and 408 stable (Positive and Negative Syndrome Scale [PANSS] total score, ⩽70) de novo participants. Participants received up to 13 monthly SC injections of RBP-7000 120 mg. Safety assessments included treatment-emergent adverse events, injection-site assessments, vital signs, laboratory and ECG parameters, extrapyramidal symptoms, and suicidality. Clinical outcomes included the PANSS and Clinical Global Impression—Severity. Findings/Results: Overall, 367 participants (73.4%) reported 1 or more treatment-emergent adverse event; the most common were injection-site pain (13.0%) and weight increase (12.8%). Most participants (>80%) experienced no injection-site reactions. No clinically meaningful changes were observed in laboratory or electrocardiogram values, vital signs, extrapyramidal symptoms, or suicidality. Over 12 months of exposure, mean PANSS scores continued to improve in rollover participants and remained stable among de novo participants. Mean Clinical Global Impression—Severity scores remained stable among all participants. Implications/Conclusions: Except for anticipated injection-site reactions, RBP-7000 demonstrated a favorable safety and tolerability profile similar to oral risperidone. Notably, PANSS scores continued to improve for participants from the pivotal study and remained stable for de novo participants. Abstract : Supplemental digital content is available in the text.